SMART VILLAGE CONCEPT TRAINING IN WEST BANDUNG REGENCY VILLAGE GOVERNMENT - Subagyo, Agus; Rohayatin, Titin; Pujilestari, Noer Apptika; Wulandari, Widuri (LPPM Univ. Ibn Khaldun Bogor, 2023)
Community service carried out aims to provide an in-depth understanding between theory and practice regarding the smart village concept. This theme was chosen because villages in West Bandung Regency have the opportunity to realize village governance with the concept of smart village government. However, until now not all villages in West Bandung Regency have realized village governance with the concept of smart village government. This is because most of the village heads in West Bandung Regency are not aware of the strategic position and advantages of the infrastructure they have and the village head's weak understanding of strategies for realizing good governance. The method of implementing community service is done by providing material, lectures, focus group discussions, and evaluations. To make the smart village run optimally, the capacity of the village government is needed. Human resources play an important role in the realization of a smart village, of course, supported by facilities and infrastructure in the village. From the results of this community service, the village government in West Bandung Regency wants to make their village smart. For this reason, village government officials hope that education and training related to smart villages are often held.